Development of Science’s e-Module Based on Qur’an Integration-interconnection and Spiritual Intelligence (QISI) for Solar System Learning - Teuku Muhammad Hary Ramadhan; A Halim; Mustanir Mustanir; Ismul Huda; Evendi Evendi; Fauzi Saleh; Fahmi Sofyan; Yusrizal Yusrizal; Safrida Safrida (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to develop a valid, practical, and effective science e-module based on QISI used in the learning process of the solar system. The research method used in this research is Research & Development (R&D) with the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). This research was conducted at SMP IT Luqmanul Hakim Aceh with a sample of 31 seventh-grade students. Sampling using a purposive sampling technique. The results showed that the validity test obtained a percentage of 87.40% with very valid criteria. In addition, the results of the practicality test by the science teachers obtained a percentage of 86.88% with very practical criteria, then the results of the practicality test by students obtained a percentage of 80.78% with practical criteria. Science e-module is effectively used in learning, with the result of obtaining an N-gain value of 0.62. So, it can be concluded that the science e-module based on QISI has been successfully developed which is very valid, practical, and effectively used in solar system learning